Review of the genus Diduga (Lepidoptera, Erebidae, Arctiinae) of Laos, with description of one new species - Bayarsaikhan, Ulziijargal; Kwon, Hyung Wook; Kim, Kil Won; Bae, Yang-Seop (Zootaxa, 2023)
The genus Diduga Moore, [1887] is reviewed with 11 species from Laos, including one new species, D. bantha sp. nov. Illustrations of adults and genitalia of all examined species from Laos are provided, with the checklist of Laotian species of the genus Diduga.